2000
DOI: 10.1007/s004670000440
|View full text |Cite
|
Sign up to set email alerts
|

Adrenomedullin and nitrite levels in children with minimal change nephrotic syndrome

Abstract: Nitric oxide (NO) serves many functions within the kidney, and recent evidence suggests that NO contributes to glomerular injury. Adrenomedullin (AM) is a novel hypotensive peptide originally isolated from human pheochromocytoma. Recent studies showed that plasma AM concentrations correlated with the extent of proteinuria. We have examined the possible role of these two agents by studying plasma and urinary total nitrite (NO-2 + NO-3) and AM levels in children with minimal change nephrotic syndrome (MCNS). In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…Trachtman et al also reported that patients with MCNS had increased urinary nitrite excretion regardless of whether the disease was in relapse or remission [6]. The present data concerning NOx in serum support the results by Balat et al and Trachtman et al [5,6]. From our studies with immunostaining, no nitrotyrosine, iNOS, or eNOS were dyed in the case that showed a particularly high NOx in serum.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Trachtman et al also reported that patients with MCNS had increased urinary nitrite excretion regardless of whether the disease was in relapse or remission [6]. The present data concerning NOx in serum support the results by Balat et al and Trachtman et al [5,6]. From our studies with immunostaining, no nitrotyrosine, iNOS, or eNOS were dyed in the case that showed a particularly high NOx in serum.…”
Section: Discussionsupporting
confidence: 93%
“…In comparison with healthy controls, children with MCNS had increased urinary nitrite excretion. Plasma nitrite levels were high in relapse compared with controls [5]. Trachtman et al also reported that patients with MCNS had increased urinary nitrite excretion regardless of whether the disease was in relapse or remission [6].…”
Section: Discussionmentioning
confidence: 96%
“…NO is also suggested to inhibit platelet activation, due to an increase in cytosolic cAMP concentration [34,35,36]. We have not found any study directly related to this problem, although there are studies detecting increased NO production in INS [37]. Further studies on the role of NO in platelet function in INS are clearly needed.…”
Section: Discussionmentioning
confidence: 79%
“…As a result, efforts have been made to identify this VPF as well as to understand the mechanism(s) for its increased release [2]. It has also been suggested that nitric oxide (NO), a typical free-radical gas synthesized from L-arginine by three isoforms of nitric oxide synthase (NOS), may be a VPF, leading to proteinuria in INS [12][13][14]. This hypothesis is based on the fact that NO has many physiological functions within the kidney, such as the regulation of vascular tone, renal hemodynamics, and modulation of fluid and electrolyte transport [15,16].…”
Section: Introductionmentioning
confidence: 99%